Le « tableau vivant » dans la genèse du projet de décor de la cathédrale de Saint-Hyacinthe de Napoléon Bourassa - Vallée, Anne-Élisabeth (RACAR : Revue d'art canadienne / Canadian Art Review, 2019)
In developing his decorative program for the Cathedral of Saint-Hyacinthe in the 1880s and 1890s, Napoléon Bourassa used staged photographs of clerics representing episodes in the life of the patron saint of the parish. This was probably the first time in his career he had done so. This photographic series calls to mind the then-widespread practice of the tableau vivant. Was Bourassa aware of this form of worldly entertainment and could it have inspired his photographic stagings? What part were these photographs supposed to play in the elaboration of his decorative project? This article offers a reflection on the tableau vivant, its place in Bourassa’s career, and its emergence in the artist’s creative process.